2007
DOI: 10.5194/nhess-7-57-2007
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami hazards in the Eastern Mediterranean: strong earthquakes and tsunamis in the East Hellenic Arc and Trench system

Abstract: Abstract. Data on tsunami phenomena occurring in the East Hellenic Arc and Trench system (HA-T) from antiquity up to the present have been updated, critically evaluated and compiled in the standard GITEC format developed in the last decade for the New European Tsunami Catalogue. New field observations are presented for the tsunamis of 9 February 1948 and 24 March 2002. From the 18 tsunamis reported eight are rather well-documented while another nine remain doubtful. The mean recurrence of strong tsunamis is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 14 publications
1
73
0
Order By: Relevance
“…There are two likely explanations for this discrepancy. Firstly, the results of Papadopoulos et al [2007] give the probabilities of tsunamis occurring somewhere in the eastern Mediterranean, whereas our results are for individual sites. Secondly, the observed catalog may contain tsunamis generated by submarine slides triggered by earthquake ground shaking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two likely explanations for this discrepancy. Firstly, the results of Papadopoulos et al [2007] give the probabilities of tsunamis occurring somewhere in the eastern Mediterranean, whereas our results are for individual sites. Secondly, the observed catalog may contain tsunamis generated by submarine slides triggered by earthquake ground shaking.…”
Section: Discussionmentioning
confidence: 99%
“…They find that in this region, landslides generate more severe tsunamis, and that earthquake generated tsunamis are limited to wave heights of up to 1-3 m. This is in good agreement with the maximum PCTA values found for the Levant coast in this study. For a larger region in the eastern Mediterranean, Papadopoulos et al [2007] consider the observed tsunami history and find a mean recurrence of strong tsunamis (maximum wave height exceeding $4 m) of $142 years. Comparable tsunami waves are found in our hazard map for 0.02 annual probability (corresponding to a mean return period of 500 years), indicating a lower hazard level than that found by Papadopoulos et al [2007].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, relatively small deviations of the growth axis angle and the differences in the lamina thickness and color seen in the stalagmite tip are largely consistent with historical earthquakes. These earthquakes, AD 334 Antioch, AD 341 Antioch, AD 344 Rhodes, and AD 365 Cyprus, had intensities of 9, 8, 9, and 9, respectively (Antonopoulos, 1980;Pararas-Carayannis, 2011;Erel and Adatepe, 2007;Papadopoulos et al, 2007;Sbeinati et al, 2005;Soloviev et al, 2000;Tinti et al, 2005). In literature, Rhodes was largely collapsed as a result of Rhodes Earthquake in AD 344.…”
Section: Sakarlakmentioning
confidence: 99%
“…The catalogue was constructed following the format of the New European Tsunami Catalogue produced by a large group of specialists in a continuing effort within the frame of the EU GITEC, GITEC-TWO and TRANSFER research projects (e.g. Tinti and Maramai, 1996;Papadopoulos et al, 2007). A characteristic case is the key earthquake and tsunami event of 544/545 AD.…”
mentioning
confidence: 99%